Preparation method and application of high-capacity cobalt-free monocrystal positive electrode material
Through three-step sintering process and additive optimization, the problems of low capacity and poor rate performance of cobalt-free high-nickel cathode materials are solved, the charge and discharge capacity and stability are improved, and more uniform particle distribution and high capacity are achieved.
Patent Information
- Application Number
- CN202311666335.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-06
- Publication Date
- 2024-12-13
Smart Images

Figure SMS_1 
Figure HDA0004591871270000011 
Figure HDA0004591871270000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cobalt-free lithium-ion batteries, and in particular to a preparation method of a high-capacity cobalt-free single crystal positive electrode material and application thereof. Background Art
[0002] With the country's strong investment in energy conservation and emission reduction, new energy vehicles and various consumer electronic products have developed rapidly. At present, new energy vehicles have gradually been recognized by the public. Lithium-ion batteries are widely used in the field of new energy vehicles due to their advantages such as good energy density, good cycle performance and good rate performance, and the demand is gradually increasing.
[0003] The core material of lithium-ion batteries is the positive electrode material, and its performance directly affects the performance indicators of lithium-ion batteries. At present, common positive electrode materials include lithium iron phosphate, lithium cobalt oxide, lithium nickel oxide, lithium-rich manganese-based and nickel cobalt manganese oxide. In particular, ternary positive electrode materials such as nickel cobalt manganese oxide NCM (NixCoyMnz) and nickel cobalt aluminum oxide NCA (NixCoyAlz) have the advantages of high energy density and good cycle performance. However, as a strategic resource, the price of cobalt element has remained high for a long time. Therefore, the cost of ternary positive electrode material lithium nickel cobalt manganese oxide (Li(Nix Coy Mn(Al)1-xy)O2) remains high, which has brought great challenges to the new energy industry and also restricted the development of ternary materials.
[0004] Cobalt-free binary cathode materials not only get rid of the constraints of cobalt, but also have advantages such as high reversible specific capacity and low price, and are increasingly favored by the energy industry. With the continuous increase in energy demand in various industries, increasing the energy density of cathode materials has become a trend. The most direct method is to increase the nickel content. For example, a Chinese patent application (publication number CN116332245A) discloses a cobalt-free high-nickel cathode material and its preparation method and application. The mechanical strength is improved by synthesizing a cathode material with a surface rich in manganese and an internal rich in nickel, but it will also lead to the existence of more lithium-nickel mixed arrangement, resulting in an increase in battery gas production, which brings risks to the safety of the battery. At the same time, the lack of Co element will lead to problems such as unstable material structure, poor low-temperature performance, and reduced life. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a method for preparing a high-capacity cobalt-free single crystal positive electrode material. By adopting a three-step sintering process combined with additives, the problem of low capacity and poor rate performance of low-nickel and cobalt-free binary products prepared by existing preparation methods is effectively solved.
[0006] On one hand, the present invention provides a method for preparing a high-capacity cobalt-free single crystal positive electrode material, which comprises at least the following steps: mixing a nickel manganese hydroxide compound with a lithium source by using a high-speed mixer, performing a primary roasting according to a primary roasting process, and obtaining a first sintered material by rolling, crushing, and sieving after the primary roasting is taken out of the furnace; mixing the first sintered material with an additive 1 by using a high-speed mixer, and then loading the material into a sagger, performing a secondary roasting according to a secondary roasting process, and obtaining a second sintered material by rolling, crushing, and sieving after the secondary roasting is taken out of the furnace; mixing the second sintered material with an additive 2 by using a high-speed mixer, and then loading the material into a sagger, performing a third roasting according to a third roasting process, and obtaining a cobalt-free positive electrode material by crushing, sieving, and demagnetizing after the material is taken out of the furnace.
[0007] As a preferred technical solution, the molar content of Ni in the nickel manganese hydroxide is 0.45-0.90, and the molar content of manganese is 0.10-0.55.
[0008] As a preferred technical solution, the lithium source is lithium carbonate or lithium hydroxide; preferably, the molar ratio of the nickel manganese hydroxide to the lithium ions in the lithium source is 1:(1-1.2).
[0009] As a preferred technical solution, the one, two and three roasting processes are as follows: roasting temperature 400-1200°C, roasting time 4-15h, and heating rate 1-6°C / min.
[0010] Preferably, the primary calcination process is as follows: calcination temperature 900-1000°C, calcination time 8-12h, and heating rate 2-4°C / min.
[0011] Preferably, the secondary calcination process is as follows: calcination temperature 900-950°C, calcination time 5-7h, and heating rate 2-3°C / min.
[0012] Preferably, the three-time calcination process is as follows: calcination temperature 400-500°C, calcination time 3-5h, and heating rate 2-3°C / min.
[0013] In the present invention, by controlling the roasting temperature, roasting time and heating rate of the primary, secondary and tertiary roasting processes and adding additives, the cobalt-free positive electrode material particles obtained after roasting are fuller and rounder, and the secondary spherical particles of the material are more evenly distributed, which effectively solves the problem that the material particles obtained by the existing preparation method have poor dispersibility and uneven size of particles, with large particles being too large and small particles being too small.
[0014] As a preferred technical solution, the additives 1 and 2 are compounds containing one or more element combinations of W, Mo, Zr, Al, Mg, Ca, Ba, Si, Ce, Sb, Ti, Nb, La, and B.
[0015] Preferably, the additive 1 is WO3, the additive 2 is a combination of boric acid and aluminum oxide, and the mass ratio of the boric acid to aluminum oxide is (0.5-2):1, preferably 1:1.
[0016] As a preferred technical solution, the additive amount of the additives 1 and 2 is 0.03-0.5wt%.
[0017] Preferably, the additive 1 is added in an amount of 0.08-0.12 wt%, preferably 0.1 wt%.
[0018] Preferably, the additive 2 is added in an amount of 0.05-0.2 wt%, preferably 0.2 wt%.
[0019] In the present invention, by controlling the addition of 0.08-0.12 wt% WO3 in the secondary calcination and adding 0.05-0.2 wt% boric acid and aluminum oxide as additives in the tertiary calcination, the charge and discharge capacity and stability of the cobalt-free positive electrode material are effectively improved.
[0020] As a preferred technical solution, the rotation speed of the high-speed mixer is 400-1000 r / min, and the mixing time is 20-40 min; preferably, the rotation speed of the high-speed mixer is 500 r / min, and the mixing time is 25 min.
[0021] Another aspect of the present invention provides an application of a method for preparing a high-capacity cobalt-free single crystal positive electrode material, which is applied to the preparation of a cobalt-free positive electrode material.
[0022] Beneficial Effects
[0023] 1. The present invention provides a method for preparing a high-capacity cobalt-free single crystal positive electrode material. By adopting a three-step sintering process in combination with additives, the problem of low capacity and poor rate performance of low-nickel and cobalt-free binary products prepared by existing preparation methods is effectively solved.
[0024] 2. In the present invention, by controlling the roasting temperature, roasting time and heating rate of the primary, secondary and tertiary roasting processes and adding additives, the cobalt-free positive electrode material particles obtained after roasting are fuller and rounder, and the secondary spherical particles of the material are more evenly distributed, which effectively solves the problem that the material particles obtained by the existing preparation method have poor dispersibility and uneven size of particles, with large particles being larger and small particles being smaller.
[0025] 3. In the present invention, by controlling the addition of 0.08-0.12 wt% WO3 in the secondary calcination and adding 0.05-0.2 wt% boric acid and aluminum oxide as additives in the tertiary calcination, the charge and discharge capacity and stability of the cobalt-free positive electrode material are effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 These are SEM characterization images of Examples 1-4, where ad in the images correspond to Examples 1-4, respectively.
[0027] Figure 2 1 is a comparison diagram of the charge and discharge curves of Example 1 and Example 2, wherein 1 is the charge and discharge curve of Example 1, and 2 is the charge and discharge curve of Example 2. DETAILED DESCRIPTION
[0028] Example 1
[0029] Embodiment 1 of the present invention provides a method for preparing a high-capacity cobalt-free single crystal positive electrode material, comprising the following steps: mixing a nickel manganese hydroxide compound with a lithium source using a high-speed mixer, performing a primary roasting according to a primary roasting process, and obtaining a fired product after the primary roasting is taken out of the furnace through rolling, crushing, and sieving; mixing the fired product with an additive 1 using a high-speed mixer and then loading it into a sagger, performing a secondary roasting according to a secondary roasting process, and obtaining a secondary roasted material after the secondary roasting is taken out of the furnace through rolling, crushing, and sieving; mixing the secondary roasted material with an additive 2 using a high-speed mixer and then loading it into a sagger, performing a tertiary roasting according to a tertiary roasting process, and obtaining a cobalt-free positive electrode material after being crushed, sieving, and demagnetizing after taking out of the furnace.
[0030] The nickel manganese hydroxide is Ni 0.6 Mn 0.4 (OH)2.
[0031] The lithium source is lithium carbonate, and the molar ratio of the nickel manganese hydroxide to the lithium ions in the lithium source is 1:1.1.
[0032] The primary calcination process is as follows: calcination temperature 960° C., calcination time 10 h, and heating rate 3° C. / min.
[0033] The secondary roasting process is as follows: roasting temperature 930° C., roasting time 6 h, and heating rate 2° C. / min.
[0034] The three-time calcination process is as follows: calcination temperature 400° C., calcination time 4 h, and heating rate 2° C. / min.
[0035] The primary, secondary and tertiary roasting devices are air atmosphere roller kilns.
[0036] The additive 1 is WO3, the additive 2 is a combination of boric acid and aluminum oxide, and the mass ratio of the boric acid to the aluminum oxide is 1:1.
[0037] The additive 1 was added in an amount of 0.1 wt %.
[0038] The additive 2 is added in an amount of 0.2 wt %.
[0039] The rotation speed of the high speed mixer is 500 r / min, and the mixing time is 25 min.
[0040] Example 2
[0041] Embodiment 2 of the present invention provides a method for preparing a high-capacity cobalt-free single crystal positive electrode material, comprising the following steps: mixing nickel manganese hydroxide and a lithium source using a high-speed mixer, performing a single roasting process, and obtaining a fired product after the single roasting is taken out of the furnace through rolling, crushing, and sieving; mixing the fired product and additive 2 using a high-speed mixer and then loading them into a sagger, performing a three-time roasting process, and obtaining a cobalt-free positive electrode material after the single roasting is taken out of the furnace through crushing, sieving, and demagnetization.
[0042] The nickel manganese hydroxide is Ni 0.6 Mn 0.4 (OH)2.
[0043] The lithium source is lithium carbonate, and the molar ratio of the nickel manganese hydroxide to the lithium ions in the lithium source is 1:1.1.
[0044] The primary calcination process is as follows: calcination temperature 960° C., calcination time 10 h, and heating rate 3° C. / min.
[0045] The three-time calcination process is as follows: calcination temperature 400° C., calcination time 4 h, and heating rate 2° C. / min.
[0046] The additive 2 is a combination of boric acid and aluminum oxide, and the mass ratio of the boric acid to aluminum oxide is 1:1.
[0047] The additive 2 is added in an amount of 0.2 wt %.
[0048] The rotation speed of the high speed mixer is 500 r / min, and the mixing time is 25 min.
[0049] Example 3
[0050] Embodiment 3 of the present invention provides a method for preparing a high-capacity cobalt-free single crystal positive electrode material, comprising the following steps: mixing a nickel manganese hydroxide compound with a lithium source using a high-speed mixer, performing a primary roasting process, and obtaining a fired product after the primary roasting is taken out of the furnace through rolling, crushing, and sieving; mixing the fired product with an additive 1 using a high-speed mixer and then loading it into a sagger, performing a secondary roasting process, and obtaining a secondary roasted material after the secondary roasting is taken out of the furnace through rolling, crushing, and sieving; mixing the secondary roasted material with an additive 2 using a high-speed mixer and then loading it into a sagger, performing a tertiary roasting process, and obtaining a cobalt-free positive electrode material after the secondary roasting is taken out of the furnace through crushing, sieving, and demagnetizing.
[0051] The nickel manganese hydroxide is Ni0.6 Mn 0.4 (OH)2.
[0052] The lithium source is lithium carbonate, and the molar ratio of the nickel manganese hydroxide to the lithium ions in the lithium source is 1:1.1.
[0053] The primary calcination process is as follows: calcination temperature 960° C., calcination time 10 h, and heating rate 3° C. / min.
[0054] The secondary calcination process is as follows: calcination temperature 850° C., calcination time 6 h, and heating rate 2° C. / min.
[0055] The three-time calcination process is as follows: calcination temperature 400° C., calcination time 4 h, and heating rate 2° C. / min.
[0056] The additive 1 is WO3, the additive 2 is a combination of boric acid and aluminum oxide, and the mass ratio of the boric acid to the aluminum oxide is 1:1.
[0057] The additive 1 was added in an amount of 0.15 wt %.
[0058] The additive 2 is added in an amount of 0.2 wt %.
[0059] The rotation speed of the high speed mixer is 500 r / min, and the mixing time is 25 min.
[0060] Example 4
[0061] Embodiment 4 of the present invention provides a method for preparing a high-capacity cobalt-free single crystal positive electrode material, comprising the following steps: mixing a nickel manganese hydroxide compound with a lithium source using a high-speed mixer, performing a primary roasting process, and obtaining a fired product after the primary roasting through rolling, crushing, and sieving; mixing the fired product with an additive 1 using a high-speed mixer and then loading it into a sagger, performing a secondary roasting process, and obtaining a secondary roasted material after the secondary roasting through rolling, crushing, and sieving; mixing the secondary roasted material with an additive 2 using a high-speed mixer and then loading it into a sagger, performing a tertiary roasting process, and obtaining a cobalt-free positive electrode material after the secondary roasting through rolling, sieving, and demagnetizing.
[0062] The nickel manganese hydroxide is Ni 0.6 Mn 0.4 (OH)2.
[0063] The lithium source is lithium carbonate, and the molar ratio of the nickel manganese hydroxide to the lithium ions in the lithium source is 1:1.1.
[0064] The primary calcination process is as follows: calcination temperature 960° C., calcination time 10 h, and heating rate 3° C. / min.
[0065] The secondary roasting process is as follows: roasting temperature 930° C., roasting time 6 h, and heating rate 2° C. / min.
[0066] The three-time calcination process is as follows: calcination temperature 400° C., calcination time 4 h, and heating rate 2° C. / min.
[0067] The additive 1 is WO3, the additive 2 is a combination of titanium oxide and aluminum oxide, and the mass ratio of titanium oxide to aluminum oxide is 1:1.
[0068] The additive 1 was added in an amount of 0.1 wt %.
[0069] The additive 2 is added in an amount of 0.2 wt %.
[0070] The rotation speed of the high speed mixer is 500 r / min, and the mixing time is 25 min.
[0071] Performance Testing
[0072] 1. The cobalt-free positive electrode materials provided in Examples 1-4 were subjected to SEM testing. The results are shown in Figure 1 By comparing the SEM images of the cobalt-free positive electrode material provided in Example 1 with the cobalt-free positive electrode material provided in Examples 2-4, it can be seen that the cobalt-free positive electrode material provided in Example 1 has fuller and rounder particles than the cobalt-free positive electrode material provided in Examples 2-4, and the secondary spherical particles of the material are more evenly distributed.
[0073] 2. The cobalt-free positive electrode materials provided in Examples 1-4 were assembled into button-type CR2032 half-cells, and electrochemical tests were performed at a current density of 0.1CC / 0.1CD at a voltage of 4.45V-3.0V. The charge and discharge curves of Example 1 and Example 2 are compared in Figure 2 The gram capacity results of button-type CR2032 half-cells assembled with the cobalt-free positive electrode materials provided in Examples 1-4 are shown in Table 1.
[0074] Table 1
[0075]
Claims
1. A method for preparing a high-capacity cobalt-free single crystal positive electrode material, characterized in that: At least the following steps are included: The nickel manganese hydroxide compound and the lithium source are mixed with a high-speed mixer, and a primary roasting process is performed. After the primary roasting is taken out of the furnace, the first sintered material is obtained by rolling, crushing and sieving; the first sintered material and additive 1 are mixed evenly with a high-speed mixer and then loaded into a sagger, and a secondary roasting is performed according to the secondary roasting process. After the secondary roasting is taken out of the furnace, the second sintered material is obtained by rolling, crushing and sieving; the second sintered material and additive 2 are mixed evenly with a high-speed mixer and then loaded into a sagger, and a third roasting is performed according to the third roasting process. After taking out of the furnace, the material is crushed, sieved and demagnetized to obtain a cobalt-free positive electrode material.
2. The method for preparing a high-capacity cobalt-free single crystal positive electrode material according to claim 1, characterized in that: The molar content of Ni in the nickel-manganese hydroxide is 0.45-0.90, and the molar content of manganese is 0.10-0.
55.
3. The method for preparing a high-capacity cobalt-free single crystal positive electrode material according to claim 2, characterized in that: The molar ratio of the nickel manganese hydroxide to the lithium ions in the lithium source is 1:(1-1.2).
4. The method for preparing a high-capacity cobalt-free single crystal positive electrode material according to claim 3, characterized in that: The primary, secondary and tertiary roasting processes are as follows: roasting temperature 400-1200° C., roasting time 4-15 hours, and heating rate 1-6° C. / min.
5. The method for preparing a high-capacity cobalt-free single crystal positive electrode material according to claim 4, characterized in that: The additives 1 and 2 are compounds containing one or more element combinations of W, Mo, Zr, Al, Mg, Ca, Ba, Si, Ce, Sb, Ti, Nb, La, and B.
6. The method for preparing a high-capacity cobalt-free single crystal positive electrode material according to claim 5, characterized in that: The additives 1 and 2 are added in an amount of 0.03-0.5 wt %.
7. The method for preparing a high-capacity cobalt-free single crystal positive electrode material according to claim 6, characterized in that: The rotation speed of the high speed mixer is 400-1000r / min, and the mixing time is 20-40min.
8. The method for preparing a high-capacity cobalt-free single crystal positive electrode material according to claim 7, characterized in that: The first roasting process is as follows: roasting temperature 900-1000°C, roasting time 8-12h, heating rate 2-4°C / min; the second roasting process is as follows: roasting temperature 900-950°C, roasting time 5-7h, heating rate 2-3°C / min; the third roasting process is as follows: roasting temperature 400-500°C, roasting time 3-5h, heating rate 2-3°C / min.
9. The method for preparing a high-capacity cobalt-free single crystal positive electrode material according to claim 8, characterized in that: The additive 1 is added in an amount of 0.08-0.12 wt %, and the additive 2 is added in an amount of 0.05-0.2 wt %.
10. An application of the method for preparing a high-capacity cobalt-free single crystal positive electrode material according to any one of claims 1 to 9, characterized in that: Used in the preparation of cobalt-free positive electrode materials.
